Developing home cleaning intervention through community engagement to reduce infections and antimicrobial resistance inGhanaian homes - Ahorlu, C.; Tsekleves, E.; Souza, D. D.; et al. (Nature Research, 2023)
Globally Antimicrobial Resistance (AMR) constitutes a health crisis, particularly in developing countries, where infectious disease are commonly fatal. There is clear evidence for microbial exposure and infection transmission within the home. Personal and environmental hygiene are the best ways of reducing household infections thus decreasing the need for antibiotics and consequently diminishing AMR. Despite this being an obvious step, research eforts to understand the home environment and its impact on AMR, cleaning and possible interventions on household cleaning are limited. We combined design and microbiology methods in an innovative mixed-method approach. A traditional survey design (n= 240), a design ethnography (n= 12), a co-design workshop and a pre-intervention microbiological dust sample analysis was undertaken to provide insights for codesign workshops in which new cleaning practices might be developed to minimise any AMR bacteria present in the household environments located in the Greater Accra Region of Ghana. Microbiological analysis of household dust showed that 36.6% of bacterial isolates detected were found to carry at least one resistance to the panel of antibiotics tested. Four scenarios were generated from an economic segmentation of the survey data. 50 ethnographic insights were ‘presented’ and descriptions of 12 bacteria species that showed resistance to one or more antibiotics (representing 176 bacterial isolates that showed resistance to one or more antibiotics found in the dust samples) were presented to the participants in a codesign workshop. An intervention, a new regime of cleaning practices agreed through the co-design workshop and practiced for thirty days, was made in (n= 7) households. The high prevalence of multidrug resistance observed in this study indicate the need for antibiotics surveillance program, not only in hospital settings but also in the household environment. There is, thus, an urgent need for targeting of interventions at the household level. Activating knowledge through community engagement in the research helps in increasing public perception and breaking down the scientist-public barrier
Research Article
Keywords: Antimicrobial resistance; High income group; Lower income group; Ghanaian homes; Community engagement